Racial inclusion in education: An Australian context - Kiran Fahd; Sitalakshmi Venkatraman (Economies, 2019)
Racism in various forms exists worldwide. In Australia, racism is inextricably linked to the history of Australian immigrants and early setters. Although the Australian education system has adopted inclusive education, evidence shows several incidents of racial exclusion. With the public education system experiencing an increased cultural diversity in student population, schools are required to develop inclusive education policies. While policies related to disability inclusion have been in practice for many years, only recently has there been an increasing awareness of racial inclusion. This research paper explores the importance of racial inclusion in education by examining the causes and effects of racial exclusion in the Australian education context. This paper considers existing practices at the national level and in schools to explore racial discrimination. It identifies the factors contributing towards racism and proposes a framework employing key strategies at the macro, meso and micro levels to achieve racial inclusion in education. It also suggests opportunities based on research to strengthen the response against racism.
Keywords: 330; education; racial inclusion; diversity; community; impact; strategies; education; racial inclusion; diversity; community; impact; strategies